TO THE 80TH JUBILEE OF PROFESSOR SEMEN I. SHERMAN - E. V. Sklyarov; D. P. Gladkochub; K. Zh. Seminsky (Геодинамика и тектонофизика, 2015)
The article is devoted to the 80th birthday of Professor Semen I. Sherman, the founder of the Laboratory of Tectonophysics in IEC SB RAS, an expert in faulting, the state of stresses, geodynamic activity and seismicity of the lithosphere, and Deputy Chief Editor of Geodynamics & Tectonophysics.